PENERAPAN ALGORITMA NAIVE BAYES DAN SVM UNTUK ANALISIS SENTIMEN BOY BAND BTS PADA MEDIA SOSIAL TWITTER - Rina Noviana; Isram Rasal (Jurnal Teknik dan Science, 2023)
BTS or Bangtan Sonyeondan is one of the vocal groups originating from South Korea, which is currently popular among Indonesian teenagers, resulting in many fans providing positive and negative comments through Twitter social media. The method used to determine whether these comments are positive or negative is by conducting sentiment analysis. The stages to perform data analysis are Preprocessing to clean the data, word weighting, labeling data into positive and negative classes, classification, and data visualization using pie charts. In this study, Naive Bayes and Support Vector Machine, were used for comparison, result of an accuracy score is 79% for Naive Bayes and 81% for Support Vector Machine. Among these two methods, Support Vector Machine achieved a higher accuracy score, and the sentiment analysis revealed that the comments obtained from Twitter users are predominantly positive.